PENDIDIKAN KRISTEN BAGI ETIKA DAN KARAKTER SISWA STUDI PADA YAYASAN SEKOLAH KRISTEN INDONESIA - Lily Haryati (SAGACITY : Journal of Theology and Christian Education, 2023)
Abstract: Christian education today is not too different from moral education. Educational institutions teach Christian Education from elementary to higher levels, so that Christian Education strived to have an impact on ethics and character of students. Christian Education in schools is not just a formality, but carries a vision and mission to build intelligent people with character and ethics. This article exposes the impact of Christian education on students' ethics and character at Yayasan Sekolah Kristen Indonesia (YSKI) in Semarang. The research used qualitative methods from the results of literacy studies, case studies, resource centered interviews and natural observations. The conclusion obtained is that the basic teaching of Christian Education according to the Bible, thus influencing the ethics and character of students to lead to the character of Christ.